Leadership, Agricultural Innovation, Peace and Order Among the Residents of the Agricultural Development of a Province - Guro, Aldrees Ansary (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the impact of leadership, agricultural innovation, and peace and order on agricultural development in Lanao del Sur. Focusing on four municipalities—Taraka, Marantao, Ganassi, and Malabang—each with unique agricultural characteristics, the study aims to understand how these factors contribute to the region's agricultural progress. A total of 399 participants were surveyed using adapted and researcher-made instruments. Descriptive-correlational and causal research designs were employed to analyze the data through mean, standard deviation, Pearson correlation, and multiple regression. The results reveal that strong leadership in political, economic, and collective agricultural actions significantly enhances development. High levels of agricultural innovation, particularly in farming methods and infrastructure, were also observed. However, the persistence of "rido" (clan feuding) and lawlessness, despite ongoing police and military efforts, continues to challenge peace and order in the province. The study concludes that while leadership and innovation drive agricultural progress, sustained efforts to maintain peace are crucial for further development.